Aetiopathogenesis of liver changes in the course of cystic fibrosis, considering disturbances of the bile acid profile as well as genetic and immunological factors - Więcek, Sabina; Woś, Halina; Grzybowska-Chlebowczyk, Urszula (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Liver changes observed in the course of cystic fibrosis comprise a group of complex processes of fibrosis, inflammation, remodelling, apoptosis and cholestasis as a result of abnormal functioning of the cystic fibrosis transmembrane conductance regulator (CFTR) protein, immunological reactions and response to oxidation stress. Liver lesions are only observed in 5–20% of patients with diagnosed cystic fibrosis; however, they increase mortality, reduce the lifespan and deteriorate the quality of life. Liver diseases are the most common extrapulmonary causes of death in patients with cystic fibrosis. The aim of the study was to analyse the hitherto performed studies on the aetiopathogenesis of liver changes in the course of cystic fibrosis considering disturbances of the bile acid profile as well as genetic and immunological factors.